Altered Salivary Enzyme Activity and Its Physiological Implications in Oral Squamous Cell Carcinoma. A Clinical Study - Ayesha Yasir, Shahzad Nasir, Muhammad Saad Shaikh, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Oral squamous cell carcinoma (OSCC) is the most common malignancy of the oral cavity and remains a major cause of morbidity and mortality, largely due to delayed diagnosis. Saliva has gained increasing attention as a non-invasive diagnostic medium because it reflects pathological and physiological alterations occurring within the oral microenvironment. Changes in salivary enzyme activity may serve as potential diagnostic and prognostic indicators of OSCC. Objective: To evaluate alterations in salivary enzyme activity and to assess their physiological significance in patients with oral squamous cell carcinoma. Methods: This clinical observational study included 59 patients with a histopathologically confirmed diagnosis of OSCC. Unstimulated whole saliva samples were collected under standardized conditions prior to the initiation of any treatment. Salivary enzyme activities, including salivary amylase, lactate dehydrogenase (LDH), and alkaline phosphatase (ALP), were measured using standard spectrophotometric methods. Enzyme levels were analyzed in relation to demographic characteristics and clinical stage of the disease. Statistical analysis was performed using appropriate tests, and a p-value < 0.05 was considered statistically significant. Results: Significant alterations in salivary enzyme activity were observed among the study participants. Salivary LDH and ALP levels were markedly elevated, particularly in patients with advanced-stage disease, while salivary amylase activity was significantly reduced. A strong correlation was noted between enzyme activity levels and clinical stage, indicating a progressive biochemical abnormality with disease advancement. Conclusion: Oral squamous cell carcinoma is significantly associated with altered salivary enzyme activity, which correlates with disease severity. Elevated LDH and ALP levels, along with reduced salivary amylase activity, reflect tumor-related metabolic and physiological disturbances. Salivary enzyme analysis shows promise as a non-invasive adjunctive tool for disease assessment and monitoring in patients with OSCC. Keywords: Oral squamous cell carcinoma; Saliva; Enzyme activity; Lactate dehydrogenase; Alkaline phosphatase; Salivary amylase